Contrasting environmental factors drive bacterial and eukaryotic community successions in freshly deglaciated soils. Issue 19 (18th November 2019) - Khan, Ajmal; Kong, Weidong; Muhammad, Said; Wang, Fei; Zhang, Guoshuai; Kang, Shichang
ABSTRACT: Glacier retreats expose deglaciated soils to microbial colonization and succession; however, the differences in drivers of bacterial and eukaryotic succession remain largely elusive. We explored soil bacterial and eukaryotic colonization and yearly community succession along a deglaciation chronosequence (10 years) on the Tibetan Plateau using qPCR, terminal restriction fragment length polymorphism (T-RFLP) and sequencing of clone libraries. The results exhibited that bacteria and eukaryotes rapidly colonized the soils in the first year of deglaciation, thereafter slowly increasing from 10 7 up to 10 10 and 10 11 gene copies g −1 soil, respectively. Bacterial and eukaryotic community changes were observed to group into distinct stages, including early (0–2 year old), transition (3–5 year old) and late stages (6–10 year old). Bacterial community succession was dominantly driven by soil factors (47.7%), among which soil moisture played a key role by explaining 26.9% of the variation. In contrast, eukaryotic community succession was dominantly driven by deglaciation age (22.2%). The dominant bacterial lineage was Cyanobacteria, which rapidly decreased from the early to the transition stage. Eukaryotes were dominated by glacier-originated Cercozoa in early stage soils, while green algae Chlorophyta substantially increased in late stage soils. Our findings revealed contrasting environmental factors driving bacterial and eukaryotic community successions. Abstract : Bacterial community succession was dominated by soil factors, among which soil moisture played a key role, while eukaryotic community succession was by deglaciation age in freshly deglaciated soils.